GAMIFIKASI PEMBELAJARAN PAI BERBASIS ZEP Quiz: ANALISIS LITERATUR TERHADAP PENINGKATAN MINAT BELAJAR SISWA DI ERA DIGITAL - Ririn Mu'tamiroh, Siti; Hamam Burhanuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student learning interest in Islamic Religious Education (PAI) learning is often less than optimal due to the use of assessments and learning media that tend to be conventional and monotonous. This study aims to analyze how student learning interest in Islamic Religious Education (PAI) learning in the digital era. Assessment innovation and the use of learning media using ZepQuiz are expected to create an interactive, enjoyable learning atmosphere and can motivate students to be more active in learning, thereby increasing student learning interest. This study uses a qualitative approach with a library research method. Research data was obtained through literature studies from various scientific journals, research articles, and relevant sources discussing gamification and the use of ZepQuiz in learning. From the results of the various literature reviewed by the researcher, gamified learning using ZepQuiz can significantly increase student learning interest, engagement, and motivation through the integration of game elements such as challenges, scores, instant feedback, and healthy competition. In addition, ZEP Quiz functions not only as an evaluation medium, but also as an interactive learning tool that encourages active participation and a fun learning experience.